DISPUTE SOLVING IN INDUSTRIAL RELATIONS BASED ON ACT NUMBER 2 YEAR 2004 - Agatha Jumiati; Dahlia Dahlia (Wacana Hukum, 2021)
Industrial relations dispute solving that managed in Act No.2 Year 2004 On Industrial Relations Dispute Solvingcan be solved by bipartite negotiation, conciliation, arbitration, mediation, and industrial relations dispute court. The principle of this matter is by putting negotiation first prior to other ways. As managed in Act No.2 Year 2004On Industrial Relations Dispute Solving everyone concerned are supposed to solve it in fast, fair, and cheap ways.